Strategi Penghimpunan Dana Wakaf Produktif di Baitulmaal Muamalat - Huzzatul Fikriyah; Muhamad Zen (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2019)
The strategy of collecting productive waqf funds is the effort of planning a person or waqf institution (nadzir) in collecting waqf funds by influencing or reminding others to release a portion of their waqf assets which are then processed by Nadzir in such a way through productive programs, so that the results can be utilized continuously to be distributed to those who are entitled to get it. The strategies carried out by BMM are direct fundraising and indirect fundraising. The results of the implementation of the strategy were managed into seven productive programs. The objective of this study was toseek how the strategy carried out BaitulmaalMuamalat in collecting productive waqf funds, knowing the implementation of what strategies are implemented BaitulmaalMuamalat and evaluating the strategy of collecting productive waqf funds. This research uses a qualitative methodology with descriptive analysis techniques. The data obtained by the institution is then processed systematically in the form of written words, archives, and oral. The results of this study are the collection through direct fundraising and indirect fundraising. They are proved to be quite good with the results of the amount of funds collected from 2011 to September 2019. It was experiencing a decrease and increase in numbers, its peak in 2019, although it has not yet closed the year the funds raised were Rp1 , 5 billion. From these data, it can be concluded that the strategy, implementation and evaluation in the process of collecting productive endowment funds in BaitulmaalMuamalat is basically good enough. However,it needs to be correction and persistence again to collect these productive endowment funds.